2023
DOI: 10.3390/atmos14050853
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of PM10 Concentration in Malaysia Using K-Means Clustering and LSTM Hybrid Model

Abstract: Following the rapid development of various industrial sectors, air pollution frequently occurs in every corner of the world. As a dominant pollutant in Malaysia, particulate matter PM10 can cause highly detrimental effects on human health. This study aims to predict the daily average concentration of PM10 based on the data collected from 60 air quality monitoring stations in Malaysia. Building a forecasting model for each station is time-consuming and unrealistic; therefore, a hybrid model that combines the k-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…It was concluded that the most important variables in the prediction of PM were its own lagged values, other air pollutants, the earth skin temperature and wind speed. A hybrid model that combines the k-means clustering technique and the long short-term memory (LSTM) was developed in [19] for the prediction of the daily average concentration of PM 10 .…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that the most important variables in the prediction of PM were its own lagged values, other air pollutants, the earth skin temperature and wind speed. A hybrid model that combines the k-means clustering technique and the long short-term memory (LSTM) was developed in [19] for the prediction of the daily average concentration of PM 10 .…”
Section: Introductionmentioning
confidence: 99%